The enchanted greenhouse - Durst, Sarah Beth (Bramble, Tor Publishing Group, 2025)
"New York Times bestselling author Sarah Beth Durst invites you to her new standalone novel nestled on a far-away island brimming with singing flowers, honey cakes, and honeyed love. The hardcover edition features beautiful sprayed edges. Terlu Perna broke the law because she was lonely. She cast a spell and created a magically sentient spider plant. As punishment, she was turned into a wooden statue and tucked away into an alcove in the North Reading Room of the Great Library of Alyssium. This should have been the end of her story . . . Yet one day, Terlu wakes in the cold of winter on a nearly-deserted island full of hundreds of magical greenhouses. She's starving and freezing, and the only other human on the island is a grumpy gardener. To her surprise, he offers Terlu a place to sleep, clean clothes, and freshly baked honey cakes-at least until she's ready to sail home. But Terlu can't return home and doesn't want to-the greenhouses are a dream come true, each more wondrous than the next. When she learns that the magic that sustains them is failing-causing the death of everything within them-Terlu knows she must help. Even if that means breaking the law again. This time, though, she isn't alone. Assisted by the gardener and a sentient rose, Terlu must unravel the secrets of a long-dead sorcerer if she wants to save the island-and have a fresh chance at happiness and love. Funny, kind, and forgiving, The Enchanted Greenhouse is a story about giving second chances-to others and to yourself"--